2014
DOI: 10.2134/agronj2013.0164
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Crop Phenology Algorithm in the Land Surface Model CN‐CLASS

Abstract: Land surface models are useful tools for estimating the contribution and response to climate change of C dynamics in various terrestrial ecosystems. In many land surface models, plant phenological algorithms are incorporated based on eld studies in forests. However, to simulate adequately the C cycle over a large area, there is a need to include and validate algorithms for other ecosystems. e Carbon and Nitrogen-coupled Canadian Land Surface Scheme (CN-CLASS) is a land surface model that has been applied succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…In their simulations, they considered only three crop species (wheat, corn, and soybean) and used a fixed planting date, which can lead to a discrepancy with observations because actual planting dates vary in time as a function of weather (Zeng et al, 2013); this discrepancy can result in an overestimation of the negative impacts of warming on crop yield, as an earlier planting date is a viable adaptation strategy in many regions of the world (Waha et al, 2013). While a newer version of CLM (CLM4-Crop; Lu et al, 2015) simulates irrigation events and CO 2 fertilization as well as biomass and vegetation growth processes, its application is also limited to three crop types (Chen et al, 2015) and is not able to mechanistically simulate irrigation efficiency. Elliott et al (2014) compared 10 GHMs and 6 global gridded crop models (GGCMs); they reported that the performance of GHMs is generally poor in the simulation of future irrigation water demand.…”
Section: Capturing Cropping Systems Within Land Surface Modelsmentioning
confidence: 99%
“…In their simulations, they considered only three crop species (wheat, corn, and soybean) and used a fixed planting date, which can lead to a discrepancy with observations because actual planting dates vary in time as a function of weather (Zeng et al, 2013); this discrepancy can result in an overestimation of the negative impacts of warming on crop yield, as an earlier planting date is a viable adaptation strategy in many regions of the world (Waha et al, 2013). While a newer version of CLM (CLM4-Crop; Lu et al, 2015) simulates irrigation events and CO 2 fertilization as well as biomass and vegetation growth processes, its application is also limited to three crop types (Chen et al, 2015) and is not able to mechanistically simulate irrigation efficiency. Elliott et al (2014) compared 10 GHMs and 6 global gridded crop models (GGCMs); they reported that the performance of GHMs is generally poor in the simulation of future irrigation water demand.…”
Section: Capturing Cropping Systems Within Land Surface Modelsmentioning
confidence: 99%
“…Phenophase and organic matter accumulation and allocation process based on physiology CLASS Carbon and nitrogen model (Chang et al, 2014) Farmland in Canada Increase the determination coefficient between simulated and observed data of NEP; More rational distribution process of organic matter.…”
Section: Impacts Of Agricultural Phenology Dynamics On Surface Biophymentioning
confidence: 99%
“…Therefore, it follows that temperature determines the progression of processes to the next developmental stage and their respective rate of development [18]. Numerous relationships have been established to portray the way temperature influences plant development [19][20][21]. These comprise degree-days, day-degrees, heat units, heat sums, thermal units, and growing degree-days [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…All these tools provide mechanisms to handle large datasets and further facilitate the distribution of information among the growing scientific community. Additional examples of efforts and software that were developed to improve agricultural modeling include the CN-CLASS [21] that was initially developed to study Carbon (C) stock in forest ecosystems but was later modified to link crop phenological development and C allocation during the growth of maize. Also, CropScape is a w eb service-based application for discovering and disseminating geospatial cropland data products for decision making [4].…”
Section: Introductionmentioning
confidence: 99%